2021
DOI: 10.1002/ijgo.13774
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes and factors affecting the clinical effects of emergency cerclage in twin pregnancies with cervical dilation and prolapsed membranes

Abstract: Objective To determine the effect of mid‐trimester emergency cerclage in women with twin pregnancies with cervical dilation and prolapsed membranes, and to identify risk factors predicting spontaneous preterm birth (sPTB) before 28 weeks, after cerclage. Methods Retrospective analysis of twin gestations with cervical dilation and prolapsed membranes treated with emergency cerclage or expectant management (2015–2020). The primary outcomes were the rate of sPTB before 28 weeks and the gestational latency. Multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…In our study, the cervical dilation was 1 to 6 cm and >50% of cases with amniotic membranes prolapsed beyond the external os. Our conclusions are consistent with Zeng et al's, 38 and we believe that in the urgent situation of cervical dilation of 4 to 6 cm and bulging membranes, ECC may be the only salvage measure for prolonging gestation and improving neonatal outcome. In addition, our study assumes that ECC performed with the combined McDonald‐Shirodkar procedure is the best option of surgical therapy in twin pregnancies in women with cervical dilation of 3 to 6 cm and prolapsed membranes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the cervical dilation was 1 to 6 cm and >50% of cases with amniotic membranes prolapsed beyond the external os. Our conclusions are consistent with Zeng et al's, 38 and we believe that in the urgent situation of cervical dilation of 4 to 6 cm and bulging membranes, ECC may be the only salvage measure for prolonging gestation and improving neonatal outcome. In addition, our study assumes that ECC performed with the combined McDonald‐Shirodkar procedure is the best option of surgical therapy in twin pregnancies in women with cervical dilation of 3 to 6 cm and prolapsed membranes.…”
Section: Discussionsupporting
confidence: 93%
“…The currently available literature lack evidence for cervical dilation of ≥4 cm, and, in 2019, the SOGC suggested that ECC may be considered in women in whom the cervix has dilated to <4 cm without contractions 10 . The only published study comparing ECC in twin pregnancies in women with cervical dilation 4 to 6 cm showed an overall positive effect on pregnancy and neonatal outcomes, 37 which indirectly supports a potential benefit of ECC in twin pregnancies in women with cervical dilation ≥4 cm.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the cervical dilation was 1-6cm and more than 50% of cases with amniotic membranes prolapsed beyond the external os. And our conclusions were consistent with Chanjuan Zeng's 38 and we believed that in the urgent situation of cervical dilation of 4-6cm and bulging membranes, ECC may be the only salvage measure for prolonging gestation and improving neonatal outcome. In addition, our study assume that ECC performed with the combined McDonald-Shirodkar procedure is the best option of surgical therapy in twin pregnancies with cervical dilation of 3-6 cm and prolapsed membranes.…”
Section: Commentsupporting
confidence: 89%
“…The currently available literature lack of evidence for cervical dilation of 4 cm or more, in 2019,SOGC 10 suggested ECC may be considered in women in whom the cervix has dilated to < 4 cm without contractions. The only published study comparing ECC in twin pregnancies with cervical dilation 4-6cm showed an overall positive effect on pregnancy and neonatal outcomes 37 , which indirectly supported a potential benefit of ECC in twin pregnancies with cervical dilation [?] 4cm.…”
Section: Commentmentioning
confidence: 99%
“…To date, in patients with acute episodes of CI, rescue cerclage placement is the only proven method for prolonging pregnancy and salvaging the fetus from late miscarriage, with neonatal survival rates of up to 71.0−82.5% 2,10,11 . In such cases, subclinical IAI/MIAC, the degree of cervical dilation at presentation, and vaginal microbial communities (dominated by G. vaginalis ) are considered to be the key determinants of clinical outcomes of rescue cerclage 9,12–17 . Particularly, regardless of whether the MIAC is present, IAI is the most documented poor prognostic factor for rescue cerclage outcomes since such patients are at higher risk for late miscarriage, preterm premature ruptured membranes (PPROM), clinical chorioamnionitis, or spontaneous preterm labor (PTL) after the cerclage placement 6,9,18,19 …”
Section: Introductionmentioning
confidence: 99%